Fusion of a bacterial cysteine desulfurase to redox-sensitive green fluorescent protein produces a highly sensitive cysteine biosensor for monitoring changes in intracellular cysteine - Damien Caubrière; Arthur de Butler; Anna Moseler; Pauline Leverrier; Jean-François Collet; Andreas J. Meyer; Nicolas Rouhier; Jérémy Couturier (Redox Biology)
Over the last two decades, the development of fluorescent probes has transformed the way of measuring physiological parameters in intact cells, including in the field of redox biology. We developed a genetically encoded biosensor called CyReB to monitor intracellular cysteine in real time. This biosensor exploits the ability of a particular bacterial cysteine desulfurase to promote the oxidation of reduction-oxidation-sensitive green fluorescent protein 2 in the presence of cysteine. The specificity, sensitivity, and the oxidation-reduction dynamics of CyReB were first investigated in vitro before its in vivo functionality was confirmed by expressing CyReB in Escherichia coli and Saccharomyces cerevisiae cells. Expressing CyReB or an inactive version in wild-type and various mutant strains of Escherichia coli showed that this sensor could be used to monitor intracellular cysteine dynamics, particularly in the context of the cysteine-cystine shuttle system. This work demonstrates how using this cysteine biosensor should provide new insights into the metabolism of cysteine and cysteine-related pathways in various model organisms.